Peculiarities of localization of mathematical software into Lithuania - Dagienė, Valentina (Lietuvos matematikos rinkinys, 2008)
In the paper experience of software localization into Lithuanian is presented. Main attention is paid to the mathematical computer aids and programs. The paper covers such problems as process of translation and adoption to language and culture requirements,mathematical notation,testing, and quality assurance.Ways of problem solutionsare presentedand discussed.All localizationcycle of mathematics computer programs including analysis of the software to be localized, and support of the localized software is presented.